The Role Of Labor Policies In Promoting Inclusive Economic Growth: A Systematic Literature Review - Nabila Mutia Sari; Inayati Nuraini Dwiputri (International Journal of Business and Quality Research, 2026)
Inclusive economic growth has become a critical issue in modern development because high economic growth does not necessarily lead to equitable distribution of societal well-being. In this context, labor policies play a strategic role as instruments for enhancing employment opportunities, worker protection, productivity, and the reduction of socioeconomic inequality. This study aims to analyze the role of labor policies in promoting inclusive economic growth through a Systematic Literature Review (SLR) approach. The study employs a qualitative method using a PRISMA-based SLR design. Research data were sourced from scientific articles in the Scopus database using the keywords “labor policies” and “qualitative.” The literature selection process was conducted through the stages of identification, screening, eligibility, and inclusion, resulting in 29 relevant articles for analysis. Data analysis was performed using a thematic analysis approach to identify patterns, themes, and relationships among the studies. The research findings indicate that labor policies contribute to inclusive economic growth through five key aspects: labor protection, human resource capacity building, reduction of economic inequality, adaptation to the digital economic transformation, and strengthening of social collaboration in policy implementation. This study also found that the main challenges in implementing labor policies include weak protection for informal workers, gender inequality, high labor market flexibility, and suboptimal integration of social and economic policies. Therefore, the government needs to strengthen policies on job training, social protection, and cross-sectoral collaboration so that economic growth not only increases economic output but also creates sustainable and equitable social welfare